PENGARUH KOMPENSASI, MOTIVASI TERHADAP KINERJA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi Kasus Pada Tenaga Harian Lepas Bagian Bahu Jalan Dinas Pekerjaan Umum Dan Tata Ruang Kabupaten Rembang) - Sari, Diana Anita; Irvani, Tryas; Nurhidayati, Anik (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2021)
This research was conducted at the Department of Public Works and Spatial Planning of Rembang Regency. The purpose of this study is to prove: (1) the direct effect of compensation on performance, (2) the direct effect of motivation on performance, (3) the indirect effect of compensation through job satisfaction on performance, (4) the indirect effect of motivation through job satisfaction on performance. Data collection techniques using a questionnaire. The population in this study were all daily workers off the shoulder of the Department of Public Works and Spatial Planning of Rembang Regency totaling 52 people with saturated sampling technique. The data analysis technique used path analysis using the Amos program. The results of this study are: (1) compensation has a significant positive effect on the performance of daily workers off the shoulder of the Department of Public Works and Spatial Planning of Rembang Regency, (2) motivation has a significant negative effect on the performance of daily workers off the shoulder of the Department of Public Works and Planning. Spatial in Rembang Regency, (3) compensation has a significant positive effect on performance through job satisfaction of daily workers off the shoulder of the Department of Public Works and Spatial Planning of Rembang Regency, (4) motivation has a significant positive effect on performance through job satisfaction of daily workers off the shoulder of the Department of Road Public Works and Spatial Planning of Rembang Regency.